Kagome staircase compounds Ni3V2O8 and Co3V2O8 studied with implanted muons - Lancaster, T; Blundell, S; Baker, P; Prabhakaran, D; Hayes, W; Pratt, F (American Physical Society, 2007)
We present the results of muon-spin relaxation (μ+SR) measurements on the kagome staircase compounds Ni3V2O8 and Co3V2O8. The magnetic behavior of these materials may be described in terms of two inequivalent magnetic ion sites, known as spine sites and cross-tie sites. Our μ+SR results allow us to probe each of these sites individually, revealing the distribution of the local magnetic fields near these positions. We are able not only to confirm the magnetic structures of the various phases proposed on the basis of bulk measurements but also to give an insight into the temperature evolution of the local field distribution in each phase.